Austria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The study describes key features of the Austrian financial system, analyzes current trends in Austrian banking, and discusses appropriate regulatory responses to the changing financial environment. In this paper, the following statistical data are presented in detail: national income and its distribution, prices, wages, production, financing of the federal deficit, debt and debt services of the federal government, monetary aggregates and lending to domestic nonbanks, interest rates, exchange rate developments, balance of payments, capital account overview, international investment position, official development assistance, and so on.